Scheduling optimization for smart microgrids considering twolevels transactions of electric vehicles and energy markets. (December 2020) - Garcia-Guarin, J; Infante, W; Alvarez, D; Rivera, S
Abstract: Smart microgrid planning poses some challenges, including bi-directional energy flow both inside and outside the smart microgrid. This research studies at the internal flow level energy transactions with the internal resources of the microgrid, and at the external flow level the energy transactions with external stakeholders to the microgrid. Electric vehicles can operate bidirectionally and participate at the internal and external level of smart microgrids. In this context, this study analyzes electric vehicles both levels. (1) At the level of internal participation, electric vehicles operate in a residential area of a microgrid that is also connected to energy storage systems and elements with uncertainty, such as photovoltaic generation systems and residential loads. Prices are set by considering operating costs within the smart microgrid. (2) The level of external participation refers to an electric vehicle station that offers three services: charging, discharging and swapping battery. Prices are stochastic and come from the spot market prices of electric vehicles. Consequently, it is proposed that the aggregator must plan the optimal scheduling for the visit scenarios of two-level stochastic electric vehicles. The system can also trade energy that come from a local and wholesale energy market. Results demonstrate that two-level operation can help to evaluate the economic impact of electric vehicles.